Understanding Meaning in the Short Story “The Open Window” by Saki Through Contextual Analysis - Mutiara Angelica Sinaga; Bernieke Damanik (Yayasan Literasi Sains Indonesia, 2026)
This study carries out a contextual analysis of Saki’s short story, “The Open Window,” employing a four-layer analytical framework that integrates historical-biographical, socio-cultural, linguistic-pragmatic, and narrative-structural dimensions of meaning. One of the potential limitations of using meaning as a foundational element in a literary analysis is that meaning is always embedded in a specific context. Thus, the study attempts to pinpoint the definitive meaning of the story in relation to its situational and psychological context. A qualitative descriptive approach is employed, drawing on selective dialogue and narrative analysis. Data relevant to contextual analysis are primarily drawn from semantics and pragmatics, with particular attention to Gricean maxim violations as mechanisms of communicative deception. The Open Window is ironically meaningful, and this meaning mostly hinges on the context and the characters’ points of view. There are contextual elements in the story that the author intentionally leaves unexplained, inviting readers to engage in active inferential interpretation. The findings demonstrate that meaning in the story is produced not through any single analytical lens but through the dynamic interaction of all four contextual layers. Contextual analysis thus offers a productive perspective on meaning that is not explicitly stated in the text, and this constitutes a valid justification for employing the technique in the analysis of literary works.